Organizational performance and change management workshop proceedings (International Institute of Rural Reconstruction, 1998)
There are endless variables in the process of change. No variable is more challenging, or more enriching, than the variable of human choice. Development organizations that support human choice participatory approaches whilst working with communities, know that these approaches bear their own seeds of success, along with the seeds of change and, often, constraint.